Molecular analysis reveals high diversity in the Hoplias malabaricus (Characiformes, Erythrinidae) species complex from different Amazonian localities - FERREIRA,Alex M. V. (2021)
ABSTRACT DNA barcoding proposes that a fragment of DNA can be used to identify species. In fish, a fragment of cytochrome oxidase subunit I (COI) has been effective in many studies with different foci. Here we use this molecular tool to provide new insights into the cryptic diversity found in the Hoplias malabaricus species complex. Popularly known as trahira, H. malabaricus is widely distributed in South America. The clade shows molecular and cytogenetic diversity, and several studies have supported the occurrence of a complex of species. We performed molecular and karyotypic analysis of H. malabaricus individuals from eight Amazonian localities to assess the diversity present in the nominal taxon, and to clarify relationships within this group. We used 12 samples in cytogenetic analyses and found two karyomorphs: 2n = 40 (20m + 20sm) (karyomorph C) and 2n = 42 (22m + 20sm) (karyomorph A). We used 19 samples in molecular analyses with COI as a molecular marker, maximum likelihood analyses, and the Kimura-2-parameter evolutionary model with bootstrap support. We found karyomorph-related differentiation with bootstrap of 100%. However, we found high molecular diversity within karyomorph C. The observed pattern allowed us to infer the presence of cryptic diversity, reinforcing the existence of a species complex.